The adoption process of payment care - An agent-based approach - Biliana Alexandrova-Kabadjova; Sara G. Castellanos; Alma L. García-Almanza (Banco de México, 2012)
We investigate the payment card's adoption rate under consumers' and merchants' awareness of network externalities, given two levels of Interchange Fees in a multiagent card market. For the purpose of our research, in multiple instances of the model (scenarios) the investigated effects are analyzed over the complete process of adoption, until the market's saturation point is achieved. For each scenario, a comparison is made between two different levels of Interchange Fees and different degrees of consumers' and merchants' awareness. We model explicitly the interactions between consumers and merchants at the point of sale. We allow card issuers to charge consumers with fixed fees and provide net benefits from card usage, whereas acquirers can charge fixed and transactional fees to merchants.
Keywords: D7; D85; G28; L13; 330; two-sided markets; financial services; network formation